2011
DOI: 10.1590/s1984-82502011000300008
|View full text |Cite
|
Sign up to set email alerts
|

Statistical optimization of dithranol-loaded solid lipid nanoparticles using factorial design

Abstract: This st�dy describes a 3 2 f�ll factorial experimental design to optimize the form�lation of dithranol (DTH) loaded solid lipid nanoparticles (SLN) by the pre�em�lsion �ltrasonication method. The variables dr�g� lipid ratio and sonication time were st�died at three levels and arranged in a 3 2 factorial design to st�dy the infl�ence on the response variables particle size and % entrapment efficiency (%��). From the statistical analysis of data polynomial eq�ations were generated. The particle size and %�� for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 15 publications
1
15
0
Order By: Relevance
“…Gambhire and others (2011) observed that higher sonication times produced smaller nanoparticles made of dithranol, Compritol 888 ATO, and Span 60 (3% (w/v)). [25] Gupta and others (2016) reported that smaller particles were obtained by increasing the time and the amplitude of the sonication step when they encapsulated an anticancer agent in glyceryl distearate nanoparticles. [26] On the contrary, other authors have found an increment of the particle size due to higher ultrasonication times or amplitude.…”
Section: Effect Of Time and Amplitude Of The Sonication Processmentioning
confidence: 99%
“…Gambhire and others (2011) observed that higher sonication times produced smaller nanoparticles made of dithranol, Compritol 888 ATO, and Span 60 (3% (w/v)). [25] Gupta and others (2016) reported that smaller particles were obtained by increasing the time and the amplitude of the sonication step when they encapsulated an anticancer agent in glyceryl distearate nanoparticles. [26] On the contrary, other authors have found an increment of the particle size due to higher ultrasonication times or amplitude.…”
Section: Effect Of Time and Amplitude Of The Sonication Processmentioning
confidence: 99%
“…This result could be attributed to the increased viscosity of the antisolvent (water) by increasing polymer molecular weight and inhibition of nanoparticle growth during solvent evaporation leading to the formation of small nanoparticles. The increased amount and molecular weight of the used polymer could also reduce the chance of nanoparticle aggregation by the formation of hydrophilic coat around the formed nanoparticles [22,23] .…”
Section: Determination Of Particle Size Count Rate and Polydispersimentioning
confidence: 99%
“…e extract was entrapped into the lipid matrix due to the structure of NLCs consisting of medium chain triglycerides with free spaces capable of holding a certain amount of the extract. Entrapment efficacy depends on the amount of the lipid, the solubility of the compounds in lipid, and the concentration of the surfactant [23,36].…”
Section: Entrapment Efficacy and Extract Loading Of Cp-loadedmentioning
confidence: 99%